Study on the Influence of Scaling‐Up in the Transesterification Process for the Synthesis of Biodegradable Monoglycerides of Fatty Acids - Roland Nagy; Rebeka Bejczi (Energy Science & Engineering)
ABSTRACT Fatty acids and monoglycerides from vegetable oils or animal fats are crucial in various industries. Monoglycerides, with their hydrophilic and hydrophobic properties, act as effective non‐ionic surfactants for oil‐in‐water emulsions. Scaling‐up the synthesis of biodegradable non‐ionic surfactants from natural sources presents challenges in maintaining physicochemical properties. This study investigates the scale‐up synthesis of biodegradable non‐ionic surfactants using sunflower oil and glycerol, focusing on properties like kinematic viscosity, acid number, and active matter content. Comparative experiments were conducted using different reactor sizes and configurations, evaluating the effects of reactor size, length‐to‐diameter (L/D) ratio, and mixer type. The results indicate that larger reactors generally reduce kinematic viscosity and active matter content. The geometric characteristics of the reactor significantly impact surfactant properties with variations in the RD/RH ratio affecting the active matter content and changes in the MPD/RD ratio influencing the water number. Based on our findings, the highest active matter content was achieved with an RD/RH ratio of 0.49 and an MPD/RD ratio of 0.95. A strong correlation was found between the active matter content and water solubility. The study underscores the importance of reactor design in optimizing surfactant properties when scaling‐up.